Mariologia Franciszka Petrarki w pieśni "Vergine bella, che di sol vestita" - Waszkiewicz, Piotr Tadeusz (Verbum Vitae, 2024)
Petrarch is often contrasted with the “Divine Poet”, Dante. His poetry focuses on the figure of Laura and his love for her, thus departing from medieval theocentrism. However, living on the boundary between two eras, Petrarch set certain trends in poetry and theology. His collection of poetry is crowned with a Mariological treasure of medieval poetry. This article seeks to delve into the theological aspect of Petrarch’s poetry in the song Vergine bella, che di sol vestita in an attempt to discover what kind of theologian and Mariologist he was. Of crucial importance is whether this song is a departure from his earlier anthropocentric perspective and, consequently, whether it represents a polemic or a point of encounter with Dante. To answer these questions, the article describes the probable context in which the Vergine bella was written and, above all, analyses selected invocations of the song, making it possible to discover references to earlier authors (from the patristic era to Francis of Assisi and Dante) and the original contribution of Petrarca himself, who, fundamentally faithful to his anthropocentric approach, sees Mary as a “human virgin” exceptionally compassionate towards human misery. It is the title Vergine humana that seems to constitute the most original note of Petrarca’s Mariology and an exciting point of his encounter with Dante.